Urinary tract infection among people living with human immunodeficiency virus attending selected hospitals in Addis Ababa and Adama, central Ethiopia - Ketema Bizuwork Gebremedhin; Ketema Bizuwork Gebremedhin; Engida Yisma; Haile Alemayehu; Girmay Medhin; Girma Belay; Shubhada Bopegamage; Wondwosson Amogne; Tadesse Eguale; Tadesse Eguale (Frontiers Media S.A., 2024)
BackgroundUrinary tract infections (UTIs) and antibacterial resistance (ABR) are important public health problems, but they are not well-studied among people living with human immunodeficiency virus (PLHIV) globally, especially in low-income countries. Therefore, it is important to regularly measure the extent of UTIs and ABR in the most susceptible populations. This study aimed to investigate the prevalence of UTIs, associated factors, bacterial causal agents, and their antibiotic susceptibility profile among PLHIV in central Ethiopia.MethodsA hospital-based cross-sectional study was conducted to recruit 688 PLHIV by a simple random sampling method. Background information was gathered through interviews, while clinical information was gathered from recent information sheets of patient charts using organized, pretested, and validated study tools. Midstream urine was collected aseptically and transported to the Microbiology Laboratory of Aklilu Lemma Institute of Pathobiology within 4 h of collection, maintaining its cold chain. Standard conventional microbial culture methods and matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) mass spectrometry were used to identify the bacterial isolates at the species level. Kirby Bauer's disk diffusion method was used to determine the antibiotic susceptibility profile of the bacterial isolates based on the interpretation guidelines of the Clinical Laboratory Standard Institute. Logistic regression models were used to examine factors associated with the occurrence of UTIs among PLHIV attending selected hospitals in Addis Ababa, and Adama.ResultsOut of 688 PLHIVs involved in the current study, 144 (20.9%) were positive for UTIs, whereas the majority were asymptomatic for UTIs. In the multivariable logistic regression analysis, only HIV RNA ≥ 200 copies/ml [AOR = 12.24 (95% CI, 3.24, 46.20), p < 0.01] and being symptomatic for UTIs during the study period [AOR = 11.57 (95% CI, 5.83, 22.97), p < 0.01] were associated with the occurrence of UTIs. The dominant bacterial species isolated were Escherichia coli (E. coli; n = 65; 43%), followed by Enterococcus faecalis (E. faecalis; n = 16; 10.6%) and Klebsiella pneumoniae (K. pneumoniae; n = 11; 7.3%). Over half of the E. coli isolates were resistant to antibiotics such as gentamicin (GM; n = 44; 67.7%), amikacin (AN; n = 46; 70.8%), nalidixic acid (NA; n = 42; 64.6%), ciprofloxacin (CIP; n = 40; 61.5%), and azithromycin (AZM; n = 45; 69.2%). All of the K. pneumoniae isolates (n = 11; 100%), (n = 6; 54.5%), and (n = 7; 63.6%) were resistant to [amoxicillin as well as amoxicillin + clavulanic acid], ceftriaxone, and sulfamethoxazole + trimethoprim, respectively. All the Staphylococcus aureus (S. aureus) isolates were resistant to cefoxitin, which implies methicillin-resistant S. aureus (MRSA).ConclusionThe high prevalence of UTIs and antibiotic resistance revealed in the current study needs public health interventions such as educating the population about preventive measures and the importance of early treatment of UTIs. Our findings also highlight the need to provide UTI screening services for PLHIV, and healthcare providers should adopt antibiotic stewardship programs to promote and ensure their appropriate and judicious use.